Incidence of mortality and its predictors among preterm neonates in nigist eleni mohammed memmorial comprehensive specialized hospital, Hossana, Ethiopia: a prospective follow-up study - Lire Lemma Tirore; Desta Erkalo; Selamu Abose; Lamesginew Mossie Melaku; Essayas Mulugeta; Abriham Shiferaw; Aklilu Habte; Menaseb Gebrehaweria Gebremeskel (BMC, 2024)
Abstract Background Preterm birth is the leading cause of neonatal mortality accounting for 35% of all neonatal deaths worldwide, and the second most frequent cause of death for under five children. Despite different efforts, preterm neonatal mortality is still persistently high in Ethiopia. Little is known about death and its predictors among preterm neonates in the study area. Objective This study is aimed at estimating the incidence of mortality and its predictors among preterm neonates admitted to the NICU of NEMMCSH. Methods and materials : A hospital-based prospective follow-up study was conducted from January to November 2022. A total of 197 preterm neonates were selected consecutively and followed. The Kaplan-Meier survival and failure curves were used to describe the proportion of deaths over time and to compare groups. The independent effects of covariates on the hazard of death were analyzed using a multivariable Cox proportional hazard model. Results Preterm neonates were followed for 1840 person-days. The mean time to death was 5.68 days (SD = 5.54). The incidence of mortality was 26.08 (95% CI: 19.65, 34.61) per 1000 person days. Preterm neonates of mothers with eclamsia (AHR = 3.03), preterm neonates who have not received KMC (AHR = 2.26), and preterm neonates who have not exclusively breastfed (AHR = 4.4) had higher hazards of death as compared to their counterparts. Conclusion and recommendation : The mean time to death was 5.68 days (SD = 5.54). The incidence of mortality was 26.08 per 1000 person days. Eclamsia, KMC, and exclusive breastfeeding were significant predictors of death among preterm neonates. The role of KMC in reducing mortality rates and improving outcomes has to be emphasized for mothers and families. Caregivers have to ensure that mothers and families receive adequate support and resources to facilitate KMC, including access to lactation support, counseling, and assistance with practical aspects of caregiving. Counseling and practical support to enhance exclusive breastfeeding initiation and continuation have to be strengthened. Special attention has to be given to the preterm neonates of mothers with eclampsia.